Exclusive surgical treatment of a primary cutaneous marginal zone lymphoma: a case report - Elisa Nunes Secamilli; Juliana Yumi Massuda-Serrano; Rafael Fantelli Stelini; Thais Helena Buffo; Paulo Eduardo Neves Ferreira Velho (Sociedade Brasileira de Dermatologia (SBD), 2022)
Primary cutaneous B-cell lymphomas are non-Hodgkin lymphomas presenting only in the skin and represent 25% of all primary cutaneous lymphomas. Based on their clinical behavior, they are classified into indolent and intermediate forms. Treatment of indolent forms includes surgery, radiotherapy, and, in extensive disease, rituximab. We report a case of a 57-year-old woman with a single nodule in the left arm treated with surgical excision with 5-mm security margins, without relapse after 36 months. Surgery is a therapeutic option in these lymphomas without compromising disease-free survival.